Study of the Gold Extraction Using Tetra N-Butyl Ammonium Chloride-Chloroform - Yuli Puspito Rini; Agus Kuncaka; Ngatidjo Hadipranoto (Indonesian Journal of Chemistry, 2001)
The existence of the AuCl4- ion in the solution as the function of pH before performing the extraction of gold in the system of tetra N-butylammonium chloride (TBACI) -chloroform has been studied. The experimental data showed that AuCl4- ion was hydrolyzed at pH 5-10 and, an amorf dark-brown precipitate was appeared at pH 11-14. Amount of gold in the solution at pH 14 before extraction was around 70%. Study of the extraction has been carried out by investigating the influence of pH and TBACI concentration on the extraction efficiency. The experimental result indicated that TBACI was very efficient extractant for the extraction of gold from aqueous halide with the efficiency higher than 99%. The extraction of Gold in the TBACI-chloroform was effective at pH 0-4 with minimum concentration of TBACI 10-3 M, and the calculated Kex (extraction constant) was 5.07x10-4.